Acceptability and Readiness of Fast-Food Personnel Toward Artificial Intelligence Financial Tools for Internal Control - Niño, Ace Gerome; Deleste, Vince Ledren; Batallones, Joshua James Zar; Bijare, Jeo Francis; De La Cruz, Francine; Germia, Kristian Jerund (Journal of Interdisciplinary Perspectives, 2025)
Despite the growing integration of artificial intelligence (AI) tools in financial operations, there is a limited understanding of how fast-food employees perceive and adapt to such technologies. This study aimed to assess the level of acceptability of artificial intelligence (AI) financial tools for internal control and their impact on the readiness of fast-food personnel, as well as the differences and relationships between acceptability and readiness. Using a quantitative-correlational research design, the study examined fast-food personnel through the Technology Acceptance Model (TAM) and Technology Readiness Index (TRI). Results revealed that both the willingness to adopt and readiness of the fast-food personnel were high, indicating a positive perception of AI financial tools. Moreover, no significant differences in acceptability were found when participants were grouped by age and job position; however, a considerable difference emerged when participants were grouped by sex in terms of ease of use, suggesting that males and females perceive AI financial tools differently. Regarding readiness, significant differences were observed in optimism and innovativeness when grouped according to sex, indicating that sex influences an individual’s level of preparedness. Lastly, a powerful and significant positive relationship was found between the respondents’ level of acceptability and readiness, implying that readiness and acceptability influence each other, suggesting that openness to AI tools and the capacity to engage with them are mutually reinforcing. These findings offer practical insights for organizational training programs and digital transformation strategies in the fast-food sector. The study recommends that owners and management provide proper formal training for personnel and identify key areas for improvement. Future research should also explore other factors that may affect acceptability and readiness.